HADIS TENTANG AL-QARDH DAN KEHARAMAN RIBA AL-QARDH - Khairul Bahri Nasution (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
Al-Qardh is an act that is recommended in Islam, which will be rewarded by Allah SWT, and includes kindness if the borrower provides additional assets or goods borrowed on a voluntary basis, not because the loan conditions are met. It contains compassionate human and social values ​​to fulfill the borrower's needs. But in reality, sometimes the muqtaridh in doing al-qardh requires the benefit of the muqridh. This problem can be motivated by ignorance of the procedures for al-qardh taught by the Prophet in his words. The hadiths regarding al-Qard are from the Prophet ﷺ even though in some of the sanad there are weaknesses, especially in the history of Ibn Majah. However, because it is supported by another Sahih hadith and especially the Qur'an in surah Al-Baqarah: 245: